Museums for all: translation and interpreting for multimodal spaces as a tool for universal accessibility - Jiménez Hurtado, Catalina; Seibel, Claudia; Soler Gallego, Silvia (MonTi Monografías de Traducción e Interpretación, 2014)
Audiovisual Translation (AVT) has a scientific responsibility to develop analytical methodologies for the textual phenomenon of multimodality, and for the translation strategies associated with it. At the same time, it should aim to provide studies of universal accessibility with a powerful tool for facilitating access to knowledge. This article offers some reflections on the theoretical foundations of AVT and considers how these are projected in the creation of new professional profiles, with specific application to universal accessibility in the museums.